Athletic trainers' job tasks and status during the COVID-19 pandemic: A preliminary analysis - Winkelmann, Z. K.; Games, K. E. (Journal of Athletic Training, 2021)
Context: In December 2019, severe acute respiratory syndrome coronavirus 2, also known as the novel coronavirus disease 2019 (COVID-19), became a global public health crisis. Government officials in the United States subsequently responded by issuing lockdown orders that closed schools, terminated sports, and resulted in many people transitioning to working from home, immediately affecting the ability of athletic trainers (ATs) to practice clinically. Objective: To describe the job status, job duties, telemedicine use, and resiliency of ATs during the COVID-19 pandemic. Design: Cross-sectional study. Setting: Mixed-methods survey. Patients or Other Participants: A total of 611 ATs (age = 32 ± 13 years). Main Outcome Measure(s): The survey consisted of 6 demographic questions, a job status assessment (3 questions, 1 open-ended prompt), a telemedicine use assessment (5 questions, 2 open-ended prompts), and the 6-item Brief Resilience Scale. Qualitative analyses were completed using Text iQ technology and descriptive statistics, and cross-tabulations were conducted using follow-up ?2 comparisons of resiliency with job setting and telemedicine use. Results: Most ATs continued to work in some capacity throughout the COVID-19 pandemic and expressed optimism about the likelihood that their job status and setting would return. However, participants shared financial and mental health concerns because of reduced pay, stress, and uncertainty about the future. We also identified versatility within the profession, as ATs were serving in new roles related to COVID-19 or adopting telemedicine (n = 251, 41.1%). Athletic trainers were implementing all domains of clinical practice using telemedicine, yet most did not consult legal counsel on or have formal training in the delivery method before implementation. Finally, most ATs exhibited normal resilience that was not affected by job setting (?2 = 26.901, P = .68) or the use of virtual health care (?2 = 2.597, P = .27). Conclusions: The COVID-19 pandemic has affected ATs' jobs, and in many cases, the ATs have demonstrated adaptability and value in assuming various roles in the larger health care system.